Does neighborhood environment influence girls' pubertal onset? findings from a cohort study - Deardorff Julianna; Fyfe Molly; Ekwaru J Paul; Kushi Lawrence H; Greenspan Louise C; Yen Irene H (BMC Pediatrics, 2012)
Abstract Background Pubertal onset occurs earlier than in the past among U.S. girls. Early onset is associated with numerous deleterious outcomes across the life course, including overweight, breast cancer and cardiovascular health. Increases in childhood overweight have been implicated as a key reason for this secular trend. Scarce research, however, has examined how neighborhood environment may influence overweight and, in turn, pubertal timing. The current study prospectively examined associations between neighborhood environment and timing of pubertal onset in a multi-ethnic cohort of girls. Body mass index (BMI) was examined as a mediator of these associations. Methods Participants were 213 girls, 6-8 years old at baseline, in an on-going longitudinal study. The current report is based on 5 time points (baseline and 4 annual follow-up visits). Neighborhood environment, assessed at baseline, used direct observation. Tanner stage and anthropometry were assessed annually in clinic. Survival analysis was utilized to investigate the influence of neighborhood factors on breast and pubic hair onset, with BMI as a mediator. We also examined the modifying role of girls' ethnicity. Results When adjusting for income, one neighborhood factor (Recreation) predicted delayed onset of breast and pubic hair development, but only for African American girls. BMI did not mediate the association between Recreation and pubertal onset; however, these associations persisted when BMI was included in the models. Conclusions For African American girls, but not girls from other ethnic groups, neighborhood availability of recreational outlets was associated with onset of breast and pubic hair. Given the documented risk for early puberty among African American girls, these findings have important potential implications for public health interventions related to timing of puberty and related health outcomes in adolescence and adulthood.